HUBUNGAN EFIKASI DIRI IBU DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS WAIHAONG, KOTA AMBON - Hana Jamaludin; Christiana Rialine Titaley; Yudhie Djuhastidar Tando; Ritha Tahitu (PAMERI, 2022)
Exclusive breastfeeding has an important role in maintaining the health and survival of babies. One of the factors that influence mothers in giving exclusive breastfeeding is the self-efficacy factor (self-confidence) in breastfeeding. Self-efficacy in breastfeeding is a mother's confidence in her ability to breastfeed or exclusively breastfeed her baby. The purpose of this study was to determine the association between maternal self-efficacy and exclusive breastfeeding for infants 0-6 months at the Waihaong Public Health Center, Ambon City. This research is an observational analytic study with a cross sectional approach conducted in July-August 2021. By using the total sampling technique, the number of samples obtained was 59 mothers of infants aged 0-6 months living in the catchment area of Waihaong Health Center. The instrument used was the BSE-SF (Breastfeeding Self-Efficacy Scale Short-Form) questionnaire. Data were analyzed using the Chi-Square method to assess the association between maternal self-efficacy and exclusive breastfeeding for infants 0-6 months. The results showed that the percentage of mothers who had a high level of self-efficacy was 61%. There were 81.4% mothers who managed to exclusively breastfed their infants in the last 24 hours. We found a statistically significant association maternal self-efficacy and exclusive breastfeeding amongst mothers with infants aged 0-6 months in the working area of ​​Waihaong Health Center (p<0.001). This study showed the importance of interventions to promote maternal self-efficacy to improve the exclusive breasting rates in the catchment area of Waihaong Health Center, Ambon City.